SEG Technical Program Expanded Abstracts 2013 2013
DOI: 10.1190/segam2013-1391.1
|View full text |Cite
|
Sign up to set email alerts
|

Time-jittered ocean bottom seismic acquisition

Abstract: Leveraging ideas from the field of compressed sensing, we show how simultaneous or blended acquisition can be setup as a -compressed sensing problem. This helps us to design a pragmatic time-jittered marine acquisition scheme where multiple source vessels sail across an ocean-bottom array firing airguns at -jittered source locations and instances in time, resulting in better spatial sampling, and speedup acquisition. Furthermore, we can significantly impact the reconstruction quality of conventional seismic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The JRM which derives from distributed compressive sensing (DCS) (Baron et al, 2009), recovers a common part and innovations with respect to the common part, leading to improved recovery of time-lapse vintages when the surveys are not replicated. The authors confirmed this observation using an example of a CS-based acquisition design-time-jittered sources in marine (Wason and Herrmann, 2013). However, accurate recovery of seismic data in CS hinges on precise knowledge of the acquisition parameters including the relative precise information on source/receiver coordinates.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The JRM which derives from distributed compressive sensing (DCS) (Baron et al, 2009), recovers a common part and innovations with respect to the common part, leading to improved recovery of time-lapse vintages when the surveys are not replicated. The authors confirmed this observation using an example of a CS-based acquisition design-time-jittered sources in marine (Wason and Herrmann, 2013). However, accurate recovery of seismic data in CS hinges on precise knowledge of the acquisition parameters including the relative precise information on source/receiver coordinates.…”
Section: Introductionmentioning
confidence: 77%
“…We consider a fixed spread seismic data acquisition with ocean bottom receivers, using time-jittered sources-a CS inspired acquisition design. Here, a receiver gather, for instance, shows overlapping shots that are unraveled and interpolated during the seismic data recovery stage (Wason and Herrmann, 2013). In the noise-free case and without calibration, Oghenekohwo et al (2014) and Wason et al (2015) showed that independent and non-replicated acquisitions lead to improved recovery of the time-lapse vintages using the JRM over IRS.…”
Section: Introductionmentioning
confidence: 99%
“…This requires a randomized sampling scheme to break the sparsity in the transform domain. There has been efforts to randomize the acquisition of seismic data (Wason and Herrmann, 2013) and it requires special acquisition design. This means vintage data that already has been shot does not satisfy the underlying assumption in sparse signal recovery.…”
Section: Introductionmentioning
confidence: 99%
“…By acquiring seismic data with simultaneous sources, larger areas can be covered in shorter acquisition times (Beasley, 2008). Wason and Herrmann (2013) have shown that data can be deblended with sparsity promotion in the curvelet domain. Since our final goal is to reconstruct up-and down-going S-waves, we implement the source separation and decomposition in a one-step approach by solving a sparsity promoting joint source separation decomposition.…”
Section: Introductionmentioning
confidence: 99%